Androgen-regulated and highly tumorigenic human prostate cancer cell line established from a transplantable primary CWR22 tumor - Dagvadorj, Ayush (2008)
PURPOSE: One of the major obstacles in understanding the molecular mechanisms underlying the transition of prostate cancer growth from androgen dependency to hormone-refractory state is the lack of androgen-regulated and tumorigenic human prostate cancer cell lines. EXPERIMENTAL DESIGN: We have established and characterized a new human prostate cancer cell line, CWR22Pc, derived from the primary CWR22 human prostate xenograft tumors. RESULTS: The growth of CWR22Pc cells is induced markedly by dihydrotestosterone (DHT), and CWR22Pc cells express high levels of androgen receptor (AR) and prostate specific antigen (PSA). Importantly, PSA expression in CWR22Pc cells is regulated by androgens. Stat5a/b, Stat3, Akt and MAPK were constitutively active or cytokine-inducible in CWR22Pc cells. The AR in CWR22Pc cells contains the H874Y mutation, but not the exon 3 duplication or other mutations. When inoculated subcutaneously into DHT-supplemented castrated nude mice, large tumors formed rapidly in 20/20 mice whereas no tumors developed in mice without circulating DHT. Moreover, the serum PSA levels correlated with the tumor volumes. When androgens were withdrawn from the CWR22Pc tumors grown in nude mice, the tumors initially shrank but re-grew back as androgen-independent tumors. CONCLUSIONS: This androgen-regulated and tumorigenic human prostate cancer cell line provides a valuable tool for studies on androgen-regulation of prostate cancer cells and on the molecular mechanisms taking place in growth promotion of prostate cancer when androgens are withdrawn from the growth environment. CWR22Pc cells provide a model system for studies on the regulation of transcriptional activity of mutated H874YAR in a prostate cancer cell context.